2015
DOI: 10.1097/rlu.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT in Anti-LGI1 Encephalitis

Abstract: Anti-LGI1 encephalitis is a subgroup of autoimmune encephalitis, characterized by memory impairments, seizures, and behavioral problems. The diagnosis can be made by clinical manifestation with a help of serum autoantibody test. There was lack of imaging studies to evaluate and monitor the disease activity by anatomical and functional information. Here, we report serial F-FDG PET/CT findings in a patient with anti-LGI1 encephalitis. Intense F-FDG uptake was initially noted in bilateral limbic system at active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 8 publications
3
25
0
2
Order By: Relevance
“…PET imaging of LGI-1 encephalitis reveals altered glucose metabolism, which may be partially relevant to disease stage, but there is a lack of large-scale longitudinal PET investigations due to its cost-effectiveness and radiation exposure. Intense 18 F-flurodeoxyglucose (FDG) uptake was initially noted in the bilateral limbic system in a sample of patients with the anti-LGI1 encephalitis antibody and active disease, and subsequently decreased and normalised, mirroring the clinical course of the disease (Park et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PET imaging of LGI-1 encephalitis reveals altered glucose metabolism, which may be partially relevant to disease stage, but there is a lack of large-scale longitudinal PET investigations due to its cost-effectiveness and radiation exposure. Intense 18 F-flurodeoxyglucose (FDG) uptake was initially noted in the bilateral limbic system in a sample of patients with the anti-LGI1 encephalitis antibody and active disease, and subsequently decreased and normalised, mirroring the clinical course of the disease (Park et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, 18 F-FDG PET/CT has been used to assess for occult malignancy as a cause for encephalitis. Recent publications have begun to explore the added value of brain 18 F-FDG PET/CT in evaluating these patients (18,(20)(21)(22). Several groups have suggested that 18 F-FDG PET/CT may be used to evaluate the efficacy of therapy (20,23).…”
mentioning
confidence: 99%
“…Furthermore, the reversion of brain functional abnormalities parallels the improvement of disease. Thus, repeated brain FDG-PET could be used to evaluate therapeutic efficacy at the follow-up visit [99,100]. As an available complementary tool, brain perfusion single-photon emission computed tomography (SPECT) is also serviceable for detecting neuronal dysfunction related to inflammatory processes or a prolonged convulsive state in autoimmune-mediated LE [101].…”
Section: Auxiliary Examinationsmentioning
confidence: 99%